Revision of Continental African Germalus (Heteroptera: Lygaeoidea: Geocoridae) - Kóbor, P.; Kondorosy, E. (Zootaxa, 2017)
Germalus species of Continental Africa are now revised including redescription of Germalus ghesquierei Schouteden 1957 and Germalus conradsi Schouteden 1957. Two new species, Germalus oroszi sp. nov. and Germalus telekii sp. nov. are described.